A Colorimetric Strategy Based on Aptamer-Catalyzed Hairpin Assembly for the On-Site Detection of Salmonella typhimurium in Milk - Sihan Chen; Xinran Zong; Jiapeng Zheng; Jiaxin Zhang; Mengyao Zhou; Qing Chen; Chaoxin Man; Yujun Jiang (Foods, 2021)
Salmonella typhimurium (S. typhimurium) is a foodborne pathogen that has caused numerous outbreaks worldwide, necessitating the development of on-site strategy to prevent early contamination. Here, we set up an enzyme-free strategy for aptamer-catalyzed hairpin assembly in which salt-induced aggregation of unmodified gold nanoparticles (AuNPs) served as a colorimetric signal output, allowing on-site detection of S. typhimurium in milk. The aptamer-functionalized magnetic beads were used as a vehicle of specifically enriching target bacteria which conjugated with target aptamer to trigger the “Y” shape catalytic hairpin assembly (Y-CHA) circuit. Due to the hairpins desorbing from the surface of AuNPs to the formation of a large amount of double-stranded DNA (dsDNA), AuNPs turned from dispersion to aggregation in the presence of S. typhimurium, resulting in a change of the colorimetric signal from red to blue-gray. The signal output showed a linear relationship for S. typhimurium over a concentration range of 102 to 106 CFU/mL, with a sensitivity of 2.4 × 102 CFU/mL under optimal conditions. The visual protocol has excellent selectivity even in the presence of other competitive bacteria and has been validated in real milk samples with a sensitivity of 2.8 × 103 CFU/mL.